Correction of the measuring system composed of the contact probe head mounted on the industrial robot. (15th November 2022) - Ostrowska, Ksenia; Sokal, Grzegorz; Krawczyk, Marcin; Kupiec, Robert; Harmatys, Wiktor; Gąska, Adam; Kowalczyk, Małgorzata; Tomczyk, Krzysztof
Highlights: Two correction methods are presented for industrial robot equipped with tactile probe head. Methods are based on measurements of material standards and application of artificial neural networks. Correction methods may be used on robots with high, standard and low geometrical accuracy. Correction methods are capable of decreasing the measuring system errors by more than 50%. Abstract: The paper presents two approaches to the correction of the automated measurement system, using the example of the anthropomorphic robot that was adapted to the coordinate measurements. The above robot is equipped with a contact head with a ruby tip, which is connected with controllers cooperating with dedicated metrology software. The head correction was only proposed for the highly repeatable robot with high geometrical accuracy, while the errors of entire measuring system was included during correction of the less accurate unit. A number of material standards, artificial neural networks, LaserTracker and laser interferometer systems were used for the purposes of such assumed task. In both cases, the measurement errors of such a system was decreased by over 50%. The proposed system corrected using presented methods allows for the automated measurement, carried out directly on the production line, without the need to purchase the expensive machines, and with the use of robots installed directly on this line.